Barriers to Routine Gynecological Care in Young Adult Females in the United States - Anne M. Clark; Mireya C. Long; Brianna M. Magnusson (Women's Health Reports)
Introduction: Well-woman exams (WWEs) are important preventive health care; however, many do not regularly receive these exams. Understanding barriers to timely care is important in improving health care delivery and health outcomes. Methods: We conducted a panel survey of 1000 U.S. females 18–30 years of age. Barriers to gynecological care were assessed in four domains: financial, practical, procedural, and health care provider related. Differences between groups were assessed using t-test and analysis of variance, and logistic regression was used to examine the association between barriers and delayed care. Results: Respondents were on an average 24.5 years old and the majority were White, non-Hispanic (63%). Respondents were categorized by WWE screening status: never screened (24%), delayed screening (>1 year) (30%), and on-time screening (46%). Those who had delayed WWE expressed higher practical, procedural, and provider barriers compared with those with on-time exams. After adjusting for other barrier types and sociodemographic characteristics, lack of insurance was associated with more than twice the odds of delayed WWE (odds ratio [OR]: 2.61 95% confidence interval [CI]: 1.41–4.92) and a one-point increase in the provider barriers mean scale was associated with nearly 60% increased odds (OR: 1.59; 95% CI: 1.16–2.17) of having delayed WWE. Conclusions: The patient experience with the health care provider, along with insurance coverage, is significantly associated with delayed WWE. These results indicate that in the presence of insurance coverage, providers have a significant role in creating an environment that supports the timeliness of WWE in young adult patients.